Efficacy of Punica granatum L. based cosmeceutical products in improving hydration and skin color - A. K., Azad; Wan Sulaiman, Wan Mohd Azizi; Daud, N.A. (Pharmaceutical Research Information Group, 2016)
Objective: This study aimed to determine the efcacy of Pomegranate based cosmeceutical product as skin whitening and hydrating agents. The study are conducted by selecting marketed pomegranate skincare Materials and methods: products which are the body shop pomegranate cream and skin food pomegranate emulsion and the subjected to applied the product every night on the back of the forearm for a duration of one month. The initial and nal reading were compared and analyzed by DermaLab® Combo Handling Techniques. This study found that both products Results: showed positive result for skin whitening and hydrating activity however their superiority in terms of efcacy cannot be made due to subject compliance issue, the formulation differences as well as other environmental factors such as drinking and sun light exposure. Findings of this study suggest that the L. would be Conclusion: Punica granatum potential skin whitening and antihydrating agent in pharmaceutical or cosmeceutical products in near future.